Is there a genuine underutilisation of skills amongst the over-qualified? - Green, F; McIntosh, S (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2002)
This paper attempts to explain why, according to the 2001 UK Skills Survey, 37% of employees are apparently over-qualified for the job that they do.